Perception of the health carries in relation to Chronic Care Model - Theis, Laís Carolini; Marinho Mikosz, Dhaniel; Rosa, Saulo Vinicíus; Tetu Moysés, Simone; Proença de Moraes, Thyago (Journal of Health Care, 2021)
Introduction: chronic non-communicable conditions represent the major cause of morbidity and mortality in the country. The Chronic Care Model was implemented in the state of Paraná as a strategy to face chronic care. Objective: to evaluate the implementation of the Chronic Care Model through the perception of health professionals. Materials and Methods: exploratory, descriptive study with a qualitative approach, carried out in a primary health care service and an outpatient specialized care service in a health region in the state of Paraná. Seven professionals from specialized care and eleven professionals from primary health care participated in the study. Data were collected through six focus group meetings, whose discussions were guided by the validated instrument for assessing the model of care for chronic conditions (IEMAC ARCHO 36), and were subjected to thematic content analysis proposed by Bardin. Results: the professionals’ reports made it possible to analyze the implementation strategy according to the six dimensions proposed by the model: organization of the health system; shared health; care model; self-care; support for decision making; and information systems. It was identified that the implementation of the model has weaknesses in terms of health indicators, map of interprofessional actions, supported self-care plan, and information systems. And advances, related to the organization of the care network, risk stratification and medicalization of the elderly. Conclusion: to achieve the effectiveness of the Chronic Care Model, it is necessary to fully develop its dimensions to guarantee quality and improve chronic care.